Teachers perceptions or supervisory beliefs and practices of instructional leaders: a case study / Rusnah Arifin @ Mohamad Yusof - Arifin, Rusnah (2014)
The purpose of the study was to examine supervisory perceptions and practices of Instructional Leaders in a secondary school in Sabak Bernam. The descriptive case study comprised 77 instructional leaders which involved 32 middle managers and 45 teachers. The study employed a mixed methods research design where data were collected using a questionnaire and semi-structured interviews. Three middle managers and three teachers were randomly selected for the semi structured interviews. The quantitative data were analyzed using Statistical Package for Social Sciences (SPSS) version 18. Frequencies, percentage, mean, standard deviation and t-test were conducted from the data. The validity and reliability of the instruments were established through experts' opinions and a pilot study. The findings revealed that there was no significant difference in the perceptions on supervisory beliefs held by middle managers and teachers. The middle managers felt they employed mainly directive and nondirective approaches (80%) most frequently during supervision whilst teachers felt that middle managers were more actually more directive (60.3%). Findings also indicated teachers preferred a more collaborative approach. Furthermore there was no significant difference between middle managers and teachers' perceptions on the supervisory practices. The study also showed that there was no significant difference in supervisory practices between experienced teachers and novice teachers but there was a significant difference in the perceptions of supervisory practices between male and female teachers. Semi-structured interviews further revealed that both middle managers and t e a c h e r s alike felt that effective clinical supervisory practices could not be implemented due to the ever-increasing teacher work load, time constraints, lack of ICT facilities and insufficient knowledge on supervision leading to misconceptions of supervision in school. While the middle managers group faced problems with senior teachers there were some teachers who questioned the credibility of supervisors as they felt they lacked the skills and competencies of being a good supervisor. Overall, the findings of this study imply that instructional leaders need to be aware of effective supervision practices so that they can work collaboratively with teachers to enhance the teaching and learning process and further provide up- skilling for teachers who need help. Based on the findings, it is recommended that future research may examine the real impact of supervisory practices on student learning outcomes. Further investigations on demographic characteristics, difference schools and intensity of the supervisory practices being carried out may be conducted in the future.